1996
DOI: 10.1029/96wr01268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Reliability of the Stream Tracer Approach to Characterize Stream‐Subsurface Water Exchange

Abstract: Stream water was locally recharged into shallow groundwater flow paths that returned to the stream (hyporheic exchange) in St. Kevin Gulch, a Rocky Mountain stream in Colorado contaminated by acid mine drainage. Two approaches were used to characterize hyporheic exchange: sub-reach-scale measurement of hydraulic heads and hydraulic conductivity to compute streambed fluxes (hydrometric approach) and reachscale modeling of in-stream solute tracer injections to determine characteristic length and timescales of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
425
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(452 citation statements)
references
References 36 publications
24
425
1
2
Order By: Relevance
“…We consider hyporheic exchange flow (HEF) as a specific process by which stream water infiltrates the subsurface and returns to the stream over relatively small distances (Harvey et al, 1996). HEFs may exhibit some variability that affects the ecological functions of groundwater and lotic ecosystems.…”
Section: Hyporheic Flow Variability In Previous Workmentioning
confidence: 99%
“…We consider hyporheic exchange flow (HEF) as a specific process by which stream water infiltrates the subsurface and returns to the stream over relatively small distances (Harvey et al, 1996). HEFs may exhibit some variability that affects the ecological functions of groundwater and lotic ecosystems.…”
Section: Hyporheic Flow Variability In Previous Workmentioning
confidence: 99%
“…All of the available models for hyporheic exchange depend on the empirical evaluation of effective exchange coefficients using data from solute transport experiments conducted at the site being modeled. A comparison of transient storage model parameters (obtained from a tracer injection) and observed subsurface flows indicated that the model does not always adequately represent actual stream-subsurface exchange [Harvey et al, 1996]. While existing models employ a single exchange coefficient, in reality, exchange is driven by multiple processes that operate at several spatial scales [Harvey and Bencala, 1993;Harvey and Fuller, 1998;Wroblicky et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Dye tracer experiments on streams in conjunction with onedimensional solute transport modeling provide estimates of the transient storage zone cross-sectional area As and the transient storage exchange coefficient a s [Stream Solute Workshop, 1990; Runkel, 1998]. With As and as, estimates can be made of residence time of main channel water within the transient storage zone [Harvey et al, 1996].…”
Section: Introductionmentioning
confidence: 99%